Taxonomic significance and evolution of homobaric and heterobaric leaves in Adesmia clade species (Leguminosae – Papilionoideae) - Palermo, Fernanda Helena [UNESP]; Fortuna-Perez, Ana Paula [UNESP]; Chain, Heloísa Beltrami [UNESP]; Pezzini, Flávia Fonseca; Lewis, Gwilym Peter; de Oliveira, Rogério Antonio [UNESP]; Rodrigues, Tatiane Maria [UNESP] (Elsevier, 2023)
The presence/absence of bundle sheath extensions (BSE) in a leaf blade allows the classification of the leaves as heterobaric or homobaric, respectively. The compartmentalization of the mesophyll by BSE is associated with differences in functional aspects of heterobaric and homobaric leaves, such as conduction of water and luminosity, traits related to the successful colonization of different environments by plants. Therefore, studies on the distribution of different leaf types in a taxon can provide information on ecological, systematic, physiological, and evolutionary aspects. The Adesmia clade belongs to the legume tribe Dalbergieae (Papilionoideae, Leguminosae) and comprises five genera with a neotropical or pantropical distribution. We mapped the distribution of Adesmia clade species with either homobaric or heterobaric leaves, searching for associations with their habit and anatomical evolution. Leaves from 75 subshrubby, shrubby, and climbing species from different environments were obtained from worldwide herbaria. Leaflet blade samples were processed according to standard techniques in plant anatomy. We found that 53.4% of the species studied presented heterobaric leaves and 46.6% presented homobaric leaves. All species of the genus Adesmia DC. had homobaric leaves, while all species of Amicia Kunth and Nissolia Jacq. had heterobaric leaves. In contrast, Zornia J.F. Gmel. and Poiretia Vent. presented some species with homobaric leaves and others with heterobaric leaves. All climbers studied had heterobaric leaves. For the shrubby and subshrubby species analysed, 64,8% had heterobaric leaves and 35,2% had homobaric leaves. Our results show that within the Adesmia clade the BSE in the leaf blade possibly evolved from heterobaric leaves with the extensions in the second and third order (occasionally fourth order) veins to heterobaric leaves with BSE only in second order veins, and for homobaric leaves in earlier lineages (Zornia and Adesmia).
Keywords: Bundle sheath extensions; Evolution; Fabaceae; Habit; Leaf anatomy